Implementación del Sistema de gestión de la Calidad basado en la norma NTC ISO 9001:2015 en la empresa L&M Ingenieros consultores S.A.S de Bogotá D.C. (2019)
For the development of this degree work we want to implement a Quality Management System based on the NTC ISO 9001: 2015 standard, the company did not have a Management System so it was necessary to make a diagnosis that allowed knowing the percentage of compliance with the company. Taking into account the results of the diagnosis, the activities that will be carried out for the implementation of the QMS in the company are established. Compliance with the Action Plan is carried out in a Gantt Chart where establish the dates and those responsible for the activities, this seeks to meet 100% of the requirements of the standard.